The Significance of At-Risk or Prodromal Symptoms for Bipolar I Disorder in Children and Adolescents. (January 2013) - Hauser, Marta; Correll, Christoph U
While in the early identification and intervention of psychosis-specific instruments and risk criteria have been generated and validated, research into indicated preventive strategies for bipolar I disorder (BD I) has only recently gained momentum. As the first signs of BD I often start before adulthood, such efforts are especially important in the vulnerable pediatric population. Data are summarized regarding the presence and nature of potentially prodromal, that is, subsyndromal, symptoms prior to BD I, defined by first-episode mania, focusing on pediatric patients. Research indicates the possibility of early identification of youth at clinical high risk for BD. Support for this proposition comes from retrospective studies of BD I patients, as well as prospective studies of community samples, offspring of BD I subjects, youth with depressive disorders, and patients at high risk for psychosis or with bipolar spectrum disorders without lifetime history of mania. These data provide essential insight into potential signs and symptoms that may enable presyndromal identification of BD I in youth. However, except for offspring studies, broader prospective approaches that focus on youth at clinical high risk for BD I and on developing specific interviews and (or) rating scales and risk criteria are mostly missing, or in their early stage. More work is needed to determine valid and sufficiently specific clinical high-risk criteria, to distinguish risk factors, endophenotypes, and comorbidities from prodromal symptomatology, and to develop phase-specific interventions that titrate the risk of intervention to the risk of transition to mania and to functional impairment or distress. Moreover, studies are needed that determine potential differences in prodromal symptoms and trajectories between children, adolescents, and adults, and the best phase-specific interventions.